A handbook of tropical soil biology : (Earthscan, 2008)
This practical handbook describes sampling and laboratory assessment methods for the biodiversity of a number of key functional groups of soil organisms, including insects, earthworms, nematodes, fungi and bacteria. The methods provide a standardized basis for characterizing soil biodiversity occurring in terrestrial natural and agro-ecosystems in the tropics and current land uses in forest and forest margin areas. The aim is to assess soil biodiversity against current and historic land use practices both at plot and landscape scales and further to identify opportunities for improved sustainable land management through the introduction and/or management of soil biota, thus reducing the need for external inputs such as fertilizers and pesticides.